ANALISA BEBAN KERJA MENTAL MENGGUNAKAN METODE NASA Task Load Index (NASA-TLX) (Studi Kasus: RS. X) - Fandi Achmad; Tutik Farihah (UIN Sunan Kalijaga Yogyakarta, 2018)
Intensive Care Units (ICUs) is an installation that held health care in the patient's clinical circumstances requiring immediate medical action to saving lives and preventing further disability, complications and mortality. 24 hours services, highly demanding tasks to support urgent therapeutic intervention, highly possibility complications, poor patients outcomes make high workload of nurses in ICUs. The objective of the study is to measure ICU nurses workload and analysis based in nurses characteristics in RS X. NASA-TLX method used to measure the workload. Based on research, the level of nurses workload in RS X are have high and very high workload. The dimension ranking of the workload from the highest to the lowest is the Temporal Demand (62), Frustration (63), Mental Demands (65), Physical Demands (69.667), Effort (76.67) and Performance (80.667).